Study on Performance, Mechanical Behaviour and Microstructural Characteristics of Eco-Friendly Limestone Calcined Clay Cement (LC3) Concrete with GGBS – A Sustainable Approach - K, Venkataraman; P R, Kannan Rajkumar (International Journal of Sustainable Construction Engineering and Technology, 2024)
Despite making a significant contribution to global carbon dioxide emissions, the cement industry is rapidly growing all over the world. Utilization of Supplementary Cementitious Materials (SCMs) is the appropriate way to lower these carbon dioxide emissions. A Limestone Calcinated Clay Cement (LC3) is a type developed with calcinated clay, limestone and clinker. The properties of LC3 concrete added with other SCM are very scanty. This study focuses on examining the workability and mechanical properties of LC3 concrete replaced with 10% GGBS for M25, M30 and M50 grade. It was noted that replacing the cement with 10% GGBS decreases compressive strength, modulus of elasticity, split tensile strength and flexural strength by 3.57%-5.84%, 1%-3.7%, 3.92% -15.92% and 7.46% -19.95% respectively. The Ultrasonic Pulse Velocity (UPV) values of the GGBS added LC3 concrete was found to be under the acceptable level. There was insignificant adverse effect on workability and mechanical properties of the GGBS added LC3 concrete. Hence, it was concluded that the LC3 cement can be replaced with 10% of GGBS to promote the more sustainable construction practices.